The Pronunciation of the Capital of Ukraine in English-Speaking Media - Lina Bikelienė (Research in Language)
Speaker identity is one of the factors that might play a role in the realisation of sounds. Previous studies have observed that phonetic variations, alongside the formation of speaker’s identity, can index political meaning. This article aims at analysing a politically conditioned variation in rendering the name of the capital of Ukraine. Though the change from ‘Kiev’ to ‘Kyiv’ precedes the beginning of the Russian war in Ukraine, the analysis shows 24 February, 2022 has accelerated the process. Contrary to the general tendency for a language change to manifest first in the spoken mode and then proceed to writing, the findings indicate faster shift from ‘Kiev’ to ‘Kyiv’ in written English.